Case Report and Literature Review: Diagnosis, Tailored Genetic Counseling and Cancer Prevention for a Locally Advanced dMMR/MSI-H/TMB-H Lung Cancer Patient With Concurrent Lynch Syndrome Mediated by a Rare PMS2 Splicing Variant (c.1144+1G>A) - Han, Quanli; Liu, Si; Cui, Zhi; Wang, Qi; Ma, Tonghui; Jiang, Liwen; Li, Xiaomo; Dai, Guanghai (Frontiers in Genetics, 2022)
Lynch syndrome (LS) is a cancer-predisposing genetic disease mediated by pathogenic mutations in DNA mismatch repair (MMR) genes MLH1, MSH2, MSH6, and PMS2. Accumulating evidence demonstrates that there is significant biological heterogeneity across MMR genes. Compared to MLH1 and MSH2, PMS2 variant carriers have a much lower risk for LS-related cancers. Tumors in MLH1 and MSH2 variant carriers often display MMR deficiency (dMMR) and/or high microsatellite instability (MSI-H), two predictive biomarkers for immunotherapy efficacy. However, tumors in PMS2 variant carriers are largely microsatellite stable (MSS) instead of MSI. Therefore, the optimal management of cancer patients with LS requires the integration of disease stage, MMR gene penetrance, dMMR/MSI status, and tumor mutational burden (TMB). In this work, we presented a locally advanced lung cancer patient with dMMR/MSI-H/TMB-H tumor and selective loss of PMS2 by immunohistochemistry. Germline testing revealed a rare PMS2 splicing variant (c.1144+1G>A) in the proband and his healthy daughter. The diagnosis of LS was made based on genetic analysis of this variant and literature review. Given the incomplete penetrance of PMS2, the proband and the carrier received precision genetic counseling. To reduce cancer risk, the proband received four cycles of nivolumab plus chemotherapy and achieved a disease-free survival of sixteen months.